1993
DOI: 10.1172/jci116621
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like growth factor-1 stimulation of lymphopoiesis.

Abstract: IntroductionWe show that treatment of adult mice with recombinant human insulin-like growth factor 1 (rhIGF-1) induces striking modifications in lymphocyte number and function. 9-mo-old male mice received rhIGF-1 (4 mg/kg per d) or its excipient by subcutaneous infusion from osmotic minipumps for 7 or 14 d. Mice were weighed daily and bled at sacrifice; the spleen and thymus were harvested and single cell suspensions were made for analysis of cell phenotype and cell number. The responses of splenocytes to mito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
99
1
3

Year Published

1997
1997
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(113 citation statements)
references
References 31 publications
(34 reference statements)
10
99
1
3
Order By: Relevance
“…Systemic administration of IGF-I significantly increased the size and cellularity of both primary and secondary lymphoid organs in rodents (Binz et al 1990, Beschorner et al 1991, Murphy et al 1992, Clark et al 1993. Furthermore, IGF-I administration enhanced immune response and altered lymphocyte survival and regeneration in thymus and spleen of dexamethasone-treated rats (Hinton et al 1995(Hinton et al , 1998.…”
Section: Effects On the Immune Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Systemic administration of IGF-I significantly increased the size and cellularity of both primary and secondary lymphoid organs in rodents (Binz et al 1990, Beschorner et al 1991, Murphy et al 1992, Clark et al 1993. Furthermore, IGF-I administration enhanced immune response and altered lymphocyte survival and regeneration in thymus and spleen of dexamethasone-treated rats (Hinton et al 1995(Hinton et al , 1998.…”
Section: Effects On the Immune Functionsmentioning
confidence: 99%
“…Administration of IGF-II also stimulates growth of the thymus and spleen, but to a lesser extent than IGF-I (Buul-Offers et al 1994, Conlon et al 1995. Overexpression of IGF-I in mice stimulates T-and B-cell development and antigen-specific IgG synthesis (Clark et al 1993, Robbins et al 1994. Overexpression of IGF-II in transgenic mice stimulated the development of phenotypically normal T-cells but not mature B-cells (Kooijman et al 1995(Kooijman et al , 1997.…”
Section: Effects On the Immune Functionsmentioning
confidence: 99%
“…Peripheral blood T and B cells and monocytes from control human donors express low levels of IGF-1R in vivo (8,9). Administration of IGF-1 increases the circulating pool of CD4 ϩ T cells and splenic B cells in mice (10,11), suggesting a role for this growth factor in myelopoietic cell expansion (12). It promotes T cell proliferation during early activation (13) and inhibits apoptosis of both immature and mature T cells through at least three distinct mechanisms (14,15).…”
mentioning
confidence: 99%
“…These data may also suggest that IGF-1 is produced by a variety of thymic cells in a paracrine/autocrine fashion independently of GH regulation. It has also been shown that administration of rhIGF-1 in mice for one to two weeks results in an increase of thymic mass by doubling T-lymphocyte population [79]. This is further evidence showing that treatment with rhIGF-1 increases thymocyte number.…”
Section: The Somatotrope Gh/igf-1 Axis and Thymus Function In Rodentsmentioning
confidence: 73%
“…The exact mechanism is not yet known, but it has been shown that GH enhances T-cell proliferation in rodents. The implantation in aged rats of pituitary GH3 cells secreting GH increases the size of their thymus and increases thymocyte numbers [79]. In GH-and prolactin-deficient dwarf DW/J mice, GH administration increases thymic cell number and T-cell proliferation [93].…”
Section: Effects On Thymocyte Numbermentioning
confidence: 99%